India and trade blocs: A gravity model analysis - Arjun SINGH; Dr. S.P. PADHI (Theoretical and Applied Economics, 2020)

(untitled)
This paper analyses the trading relationship of India with major trade blocs which includes EU, NAFTA and ASEAN weather the trade flow indeed affected by the GDP (Income), Distance, tariff and per capita GDP by using gravity model on the panel data from the period of 1991 to 2017. The panel data is examined by the Multi-level mixed effect model with linear regression and ML method of estimation is used for estimating the model. The study will attempt to examine the trade bloc which has significant trade with India as per the gravity model is a concern. The study found that the distance negatively affecting the trade flow for EU and NAFTA which is as per theoretically expectations while in case of ASEAN its positively affecting the trade flow which is not as per theoretical expectations, However the coefficient is not significant. GDP is negatively and insignificantly affecting the trade flow between India and ASEAN and NAFTA whereas GDP is negatively and significantly affecting the trade flow between India and EU.